On suppression of chaotic motions of a portal frame structure under non-ideal loading using a magneto-rheological damper - Tusset, Angelo Marcelo; Piccirillio, Vinicius; Balthazar, José Manoel [UNESP]; Brasil, Reyolando Manoel Lopes Rebello da Fonseca (My University, 2015)
We consider chaotic motions of a portal frame structure under non-ideal loading. To suppress this chaotic behavior, a controlling scheme is implemented. The control strategy involves application of two control signals and nonlinear feedforward control to maintain a desired periodic orbit, and state feedback control to bring the system trajectory into the desired periodic orbit. Additionally, the control strategy includes an active magneto-rheological damper to actuate the system. The control force of the damper is a function of the voltage applied in the coil of the damper that is based on the force given by the controller.
Keywords: Feedback control; Feedforward control; MR damper